C-level managers and born-digitals' scaling: The case of Initial Coin Offerings (ICOs) - Gartner, Johannes; Moro, Andrea (Elsevier, 2023)
This research contributes to the Management of Technology (MOT) literature by scrutinizing the interrelation between education, experience, and the scaling aptitudes of high-tech companies. The study hinges on a comprehensive analysis of data collected from 1987 C-level executives and 3644 born-digital firms that pursued funding via blockchain-based Initial Coin Offerings (ICOs). Employing structural equation modeling, we systematically tested our hypotheses, contrasting the scaling trajectories of companies that successfully procured funding against those that fell short. Our findings reveal that amongst the diverse managerial competencies, only the leadership acumen of CEOs plays an important role in fostering the scaling of tech-companies across the spectrum, leaving the proficiencies of CFOs and CTOs with negligible impact. More crucially, the competencies of a CEO magnify in importance in relation to a tech-company's scaling potential post the securing of funds. The insights gained from this study not only enrich the existing body of knowledge on scaling and ICOs within the MOT literature but also hold considerable practical value for crafting effective scaling strategies in the high-tech industry.
Keywords: Management of Technology; Scaling; Born-digital; Initial Coin Offering (ICO)